SOCIODEMOGRAPHIC CHARACTERISTICS, WORK VENUE, KNOWLEDGE, AND CONDOM USE WITH CLIENTS AMONG INDIRECT FEMALE SEX WORKERS IN DENPASAR, BALI, INDONESIA - Putra, I Gusti Ngurah Edi; Phuengsamran, Dusita; Jampaklay, Aree; Thammawijaya, Panithee; Januraga, Pande Putu (Proceedings of the International Conference on Applied Science and Health, 2018)
Introduction: Female sex workers (FSWs) remain an important key population affected by HIV&AIDS in Indonesia. Indirect FSWs, in particular, are exposing to higher risk comparing to direct FSWs due to their characteristics and working conditions that could be barriers to safe sex or consistent condom use. This study aimed to identify association between sociodemographic characteristics, work venue, and knowledge on HIV&AIDS toward condom use among indirect FSWs. Methods: This was a cross-sectional study using secondary data from a survey on indirect FSWs conducted by Center for Public Health Innovation (CPHI), Udayana University, Indonesia during August to October 2017. About 171 indirect FSWs were eligible for this analysis. The dependent variable in this study was consistent condom use during the last month. Independent variables consisted of socio-demographic characteristics, work venue, and knowledge on HIV&AIDS. Data were analysed using univariate and multivariate analysis. Results: About half of indirect FSWs (50.17%) reported using condom consistently with their clients during the last month. Indirect FSWs were more likely to use condom consistently if they completed senior high school or higher (OR=3.49; 95%CI=1.42-8.57), but less likely to use condom if they were currently or ever married compared to single ones (OR=0.23; 95%CI=0.06-0.82). Those who worked in karaoke, cafe, and bar were less likely to use condom consistently compared to those in massage parlor, spa, and beauty salon (OR=0.09; 95%CI=0.03-0.26). Conclusions: Level of consistent condom use was low, indicating the need to intensify HIV prevention to indirect FSWs. Significant determinants of consistent condom use included marital status, educational level, and work venue. This study informed that providing HIV&AIDS information and improving negotiation skill that fit with characteristics of indirect FSWs and giving institutional support at workplace is crucial to ensure consistent condom use among indirect FSWs.Â